2015
DOI: 10.1128/aac.00547-15
|View full text |Cite
|
Sign up to set email alerts
|

The Ribosomal S10 Protein Is a General Target for Decreased Tigecycline Susceptibility

Abstract: e Tigecycline is a translational inhibitor with efficacy against a wide range of pathogens. Using experimental evolution, we adapted Acinetobacter baumannii, Enterococcus faecium, Escherichia coli, and Staphylococcus aureus to growth in elevated tigecycline concentrations. At the end of adaptation, 35 out of 47 replicate populations had clones with a mutation in rpsJ, the gene that encodes the ribosomal S10 protein. To validate the role of mutations in rpsJ in conferring tigecycline resistance, we showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
100
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 112 publications
(104 citation statements)
references
References 19 publications
3
100
1
Order By: Relevance
“…5A). Consistent with previous observations (Beabout et al 2015), the most common site for significant associations was K57 (Fig. 5B).…”
Section: Gwas Identifies Putative Novel Resistance Determinantssupporting
confidence: 91%
See 1 more Smart Citation
“…5A). Consistent with previous observations (Beabout et al 2015), the most common site for significant associations was K57 (Fig. 5B).…”
Section: Gwas Identifies Putative Novel Resistance Determinantssupporting
confidence: 91%
“…The mutations significantly associated with resistance (rpsJ-K57MQR, Y58D and D60Y) have been observed in S. aureus or E. faecium in a previous experimental evolution study which selected for resistance to tigecycline. Allelic replacement to verify these mutations have failed to produce a viable mutant (Beabout et al 2015;Cattoir et al 2015). Studies in Neisseria gonorrhoeae have also described a V57M intermediate resistance mutation in the corresponding site (Hu et al 2005).…”
Section: Gwas Identifies Putative Novel Resistance Determinantsmentioning
confidence: 99%
“…116 Analysis of resistant strains found that the changes in S10 are clustered in an extended loop of the protein that lies in close proximity to the tigecycline binding site of the 16S rRNA, possibly interfering with access to or binding of its target. 117 Even modest increases in the tigecycline MIC are problematic in serious infections such as bacteremia or endocarditis because of the low achievable serum concentration of this antibiotic.…”
Section: Glycylcyclinesmentioning
confidence: 99%
“…T igecycline (TGC) resistance in Staphylococcus aureus is a rare phenomenon that has been associated with overexpression of a multidrug and toxic compound extrusion (MATE) family efflux pump (mepA) in passaged mutants and clinical strains (1,2). Recently, specific mutations on the tip of the extended loop of the ribosomal S10 protein (rpsJ) in close proximity to the 16SrRNA TGC-binding site have also been associated to TGC-resistance in passaged mutants (3). But, as far as we know, there are no studies reporting clinical S. aureus isolates with mutations at rpsJ.…”
mentioning
confidence: 99%